Spray deposited fluoropolymer/multi-walled carbon nanotube composite films with high dielectric permittivity at low percolation threshold - Zhao, X; Koos, A; Chu, B; Johnston, C; Grobert, N; Grant, P (2009)
High performance perfluoro alkoxy (PFA) and chemical vapor deposition-grown multi-walled carbon nanotube (MWCNT) composite films with thicknesses of 30 μm were prepared using a scalable spray deposition technique. A homogeneous distribution of MWCNTs within the PFA matrix was confirmed by electron and optical microscopy. Dielectric and AC conductivity measurements showed a significant enhancement of dielectric permittivity for PFA/MWCNT films at low frequencies, and a very weak dependence of dielectric permittivity on temperature in the range 25-230 °C. Very low percolation threshold volume fractions of ca. 0.0043 and 0.0017 were attained for MWCNTs with two different aspect ratios, which have been explained by an inherent feature of spray route, a microcapacitor model and percolation theory. The combination of PFA/MWCNT composites and the spray deposition route provides a promising approach for the fabrication of industrial scale composite films with well-controlled dielectric properties for micro-electronic and high temperature applications. © 2008 Elsevier Ltd. All rights reserved.